Biomaterials and Implant Biocompatibility - Cîmpean, Ani?oara (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The scientific advances in life sciences and engineering are constantly challenging, expanding, and redefining concepts related to the biocompatibility and safety of medical devices. New biomaterials, new products, and new testing regimes are being introduced to